Porosity profiles of sediments in Atacama Trench and adjacent abyssal plains - Ronnie N Glud (PANGAEA, 2024)
Sediment cores were recovered by multiple corers. Upon recovery, sediment cores were brought to a thermoregulated room kept at in situ temperature, here sediment cores were sectioned in predefinded sediment horizons and frozen for later analysis. On land, the frozen sediment was thawn and homogenized. Water contents of the respective samples were determined as the weight loss after 24 h at 105°C and wet density from the weight of a given sample volume. Porosity was calculated from the two measured parameters.